Stock Returns Following Large One-Day Declines: Evidence on Short-Term Reversals and Longer-Term Performance. - Cox, Don R; Peterson, David R (Journal of Finance, 1994)
The authors examine stock returns following large one-day price declines and find that the bid-ask bounce and the degree of market liquidity explain short-term price reversals. Further, they do not find evidence consistent with the overreaction hypothesis. The authors observe that securities with large one-day price declines perform poorly over an extended time horizon.